Posterior Reversible Encephalopathy Syndrome and Anti-Angiogenic Therapy. (September 2014) - Lam, Justina Yick Ching; Ng, Matthew Chau Hsien
Posterior reversible encephalopathy syndrome (PRES) is a clinico-radiological entity first described in 1996 by Hinchey et al, most commonly associated with hypertensive encephalopathy, eclampsia in pregnant women, immunosuppressants and cytotoxic agents. In recent years, anti-angiogenic agents as a novel class of anti-cancer therapies have become a standard of care for certain tumours. Correspondingly, there have been an emerging number of case reports documenting PRES associated with these anti-angiogenic therapies. As the manifestations of PRES are often non-specific, but could rarely lead to permanent neurological disability or even death, it is crucial that physicians are aware of PRES in relation to anti-angiogenic therapy to promptly institute appropriate management to achieve the best outcomes for patients.